Toxic Effects of Thallium on Biological Indicators of Haplic Chernozem Health: A Case Study - Sergey Kolesnikov (MDPI AG, 2021)
Thallium (Tl) was introduced into Haplic Chernozem in the amounts of 3, 30, and 300 mg/kg, and biological indicators were observed at 10, 30, and 90 days after incubation in the laboratory experiment. An increase in biological activities; i.e., the total number of bacteria, Azotobacter spp. abundance, enzymes (catalase, dehydrogenases), and phytotoxic indicators (germination rate of radish) after 30 days of Tl exposure were noted. The total number of bacteria and Azotobacter spp. abundance, enzyme activity, and phytotoxicity were more sensitive (16–76%) and informative (12–65%) indicators compared to the control, respectively. Integral biological indicators of soil state (IIBS) noted at 10, 30, and 90 days decreased at a dose of 30 and 300 mg/kg by 13–43% in relation to the control. An increase in Tl concentration and duration of exposure (up to 90 days) inhibited biological properties and caused ecotoxicological effects, respectively. We concluded that the use of individual indicators served as an indicator of the state of the soil.